2020
DOI: 10.1103/physrevapplied.13.024081
|View full text |Cite
|
Sign up to set email alerts
|

Superscattering from Subwavelength Corrugated Cylinders

Abstract: Wave scattering from a cylinder with a tensor impedance surface is investigated based on the Lorentz-Mie theory. A practical example of such a cylinder is a subwavelength metallic rod with helical dielectric-filled corrugations. The investigation is performed with the aim to maximize scattering cross-section by tailoring the surface impedance of cylindrical scatterers. For the normally incident TEz and TMz waves the required surface impedance of a subwavelength cylinder can be produced by longitudinal (axial) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The coupling between spatial harmonics becomes weak for large number N of corrugations. In this case, the contribution from high-order harmonics to the membrane function can be neglected and one is led to an approximation called the surface impedance model (SIM) [19,22,[42][43][44].…”
Section:  mentioning
confidence: 99%
“…The coupling between spatial harmonics becomes weak for large number N of corrugations. In this case, the contribution from high-order harmonics to the membrane function can be neglected and one is led to an approximation called the surface impedance model (SIM) [19,22,[42][43][44].…”
Section:  mentioning
confidence: 99%
“…In many conventional structures, the fundamental natural resonances are separated in frequency and do not spectrally overlap significantly. In recent years however there has been a growing interest in the use of tailored systems where two or more resonant modes can be superimposed or 'stacked'-made to share a resonant frequency, leading to enhanced interaction with electromagnetic radiation and improved directivity in the farfield [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The combination of the lowest order (dipole) modes-a Huygens source, has been widely explored [3,4,[11][12][13][14][15], but the stacking of higher order modes has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Mode stacking has enabled significant progress in controlling the power and directionality of radiation scattered by resonant particles when illuminated by a plane wave, which is key for technologies from light trapping in solar cells [17,18] to radar detection [19]. The spectral overlap of two or more modes in a variety of geometries has produced powerful scattering, that surpasses the theoretical single channel limit [20] in both the microwave [1,2,15] and optical regimes [14,21] as well as producing directional emission and suppressed backscatter. The opposite case, where backscattered power is maximized, has also been posited theoretically by Liberal et al [22] and Nagarhi et al [23] who demonstrated that overlapping modes with equivalent phase of radiation in the reverse direction leads to a maximization of backscattered power, which has been recently experimentally verified by the authors [16].…”
Section: Introductionmentioning
confidence: 99%
“…Scattering manipulation lays the foundation of modern photonics, which has outstanding prospects in wavefront manipulation, optical signal processing, energy collection, and sensing. In recent years, one of the main focuses in nanophotonics is to manipulate the optical scattering in order to obtain novel properties unavailable for traditional optical materials and structures [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%